2020
DOI: 10.3390/coatings10121265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot-Dip Galvanizing Process on Selective Oxidation and Galvanizability of Medium Manganese Steel for Automotive Application

Abstract: A medium manganese steel with 7.5 wt.% Mn for automobile application was galvanized in a continuous Hot Dip Galvanizing (HDG) simulator under different galvanizing conditions. It was shown that the effects of dew point, annealing temperature and annealing atmosphere on the surface oxidation of steel could be comprehensively evaluated by the consideration of oxygen partial pressure P(O2). Although Mn2SiO4 was a thermodynamic stable phase when P(O2) varied from 10−28 to 10−21 atm, it was difficult to form Mn–Si–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The effect of process atmosphere pO 2 on the selective oxidation of application-oriented med-Mn steels has not been extensively researched. 25,26,32,33 Moreover, although recent research has shown that a martensitic starting microstructure is more robust in achieving 3G AHSS target mechanical properties, 4,[8][9][10][11][12]34 there has been scarce literature on the effect of process atmosphere pO 2 on selective oxidation during the austenitizing heat treatments necessary to produce the martensitic starting microstructure. For example, the current authors have documented the microstructural evolution and mechanical property development of a prototype med-Mn steel (0.2C-6Mn-1.5Si-0.5Al-0.5Cr wt%) and have reported that CGLcompatible intercritical annealing (675 °C × 120 s) from a martensitic starting microstructure was successful in producing 3G AHSS target mechanical properties (i.e., UTS × TE ≈ 26,900 MPa%).…”
mentioning
confidence: 99%
“…The effect of process atmosphere pO 2 on the selective oxidation of application-oriented med-Mn steels has not been extensively researched. 25,26,32,33 Moreover, although recent research has shown that a martensitic starting microstructure is more robust in achieving 3G AHSS target mechanical properties, 4,[8][9][10][11][12]34 there has been scarce literature on the effect of process atmosphere pO 2 on selective oxidation during the austenitizing heat treatments necessary to produce the martensitic starting microstructure. For example, the current authors have documented the microstructural evolution and mechanical property development of a prototype med-Mn steel (0.2C-6Mn-1.5Si-0.5Al-0.5Cr wt%) and have reported that CGLcompatible intercritical annealing (675 °C × 120 s) from a martensitic starting microstructure was successful in producing 3G AHSS target mechanical properties (i.e., UTS × TE ≈ 26,900 MPa%).…”
mentioning
confidence: 99%
“…It can be seen that the oxide layer is mainly rich in Fe and O elements, while the location of the "pores" is poor in Fe and O. Compared with the oxidation of steel materials [22][23][24], the surface oxide layer of those materials is relatively continuous during the oxidation process, and there are no similar "pores." Considering that Fig.…”
Section: Morphology Of the Oxide Layermentioning
confidence: 99%
“…However, during continuous hot-dip galvanizing process, the zinc bath is often saturated with iron and hot-dip galvanizing slag inevitably precipitates. This slag is composed of Fe-Zn, Fe-Al, or Fe-Al-Zn intermetallic compounds formed at high temperatures between the dissolved Fe and molten Zn in the zinc bath or with the addition of Al to the zinc bath [7][8][9][10]. For the batch hot-dip galvanizing process, because its aluminum content is much lower, the Fe-Al phase slag will not be formed in the galvanizing bath, and only the hard zinc of Fe-Zn intermetallic compounds will be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study only focuses on the continuous hot-dip galvanizing process. In production, hot-dip galvanizing slag is generally removed by manual or mechanical methods since it harms the surface quality of the galvanizing layer [9][10][11][12]. Approximately 12% to 15% of metal zinc is inevitably carried in the process of fetching slag, resulting in a significant increase in galvanizing costs.…”
Section: Introductionmentioning
confidence: 99%